2020
DOI: 10.1177/1049909120946266
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Knowledge of Palliative Care Among US Adults: Findings From 2018 Health Information National Trends Survey

Abstract: Background: Public knowledge and awareness of palliative care (PC) is important to its effective use. However, it remains unclear whether the geographic variation in knowledge of PC exits in the United States. This study examined the national geographic variation in knowledge of PC. Methods: The study sample was obtained from the 2018 National Cancer Institute’s Health Information National Trends Survey. Basic knowledge of PC, goal concordant treatment, misconceptions, and primary information source of PC were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Palliative care is an evidence-based model that improves outcomes for people with serious illness, but it is underused in many regions of the country, with generally poorer access in community-based settings and for some racial/ethnic minority groups. 47 Additional efforts are needed to expand access to and use of these services across settings and throughout the course of serious illness, regardless of prognosis. The National Academy for State Health Policy has documented improved care and reduced unnecessary costs for people with serious illness who used palliative care.…”
Section: Approaches To Changementioning
confidence: 99%
“…Palliative care is an evidence-based model that improves outcomes for people with serious illness, but it is underused in many regions of the country, with generally poorer access in community-based settings and for some racial/ethnic minority groups. 47 Additional efforts are needed to expand access to and use of these services across settings and throughout the course of serious illness, regardless of prognosis. The National Academy for State Health Policy has documented improved care and reduced unnecessary costs for people with serious illness who used palliative care.…”
Section: Approaches To Changementioning
confidence: 99%
“…Our findings are consistent with other health services research which has found that most individuals in the US are not aware of PC. 13,15 Moreover, new insights were discovered, revealing just how widespread the lack of non-PC clinician buy-in is to engage PC teams in the care of their patients. This is worrisome since clinicians are patients' primary sources of information, and current PC education strategies have been minimally effective.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of PC knowledge in the US, with over 70% of the population stating they have no knowledge of PC. 13 The lack of PC knowledge is even more prevalent in minority populations. 14 PC misconceptions persist, such as associating PC with death, equating PC to hospice care, and believing that receiving PC requires stopping all other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study on the general population of Northern Ireland showed that only 20% knew the accurate term, “palliative care” [ 26 ]. Similarly, only 29% of adults in the United States expressed good knowledge regarding palliative care [ 28 ]. In addition, only 29% of the patients reported good palliative care knowledge in Zimbabwe [ 29 ] and Saudi Arabia [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a study on the general population of Northern Ireland showed that only 20% knew the accurate term, "palliative care" [26]. Similarly, only 29% of adults in the United States expressed good knowledge regarding palliative care [28]. In addition, only 29% of the patients reported Table 3 Attitude of patients with advanced cervical cancer towards palliative care, 2019 (N) Items with a negative attitude towards palliative care; values for these items were reversed before analysis.…”
Section: Discussionmentioning
confidence: 99%